Digitalization and the Merdeka Belajar Reform: a Policy Discourse Analysis Through Postmodern and Critical Lenses - Yunita Endra Megiati; Nandang Hidayat; Didi Sutisna (Sean Institute, 2025)
This study examines the discourse of digitalization within Indonesia’s Merdeka Belajar education reform through the lens of critical theory and postmodern philosophy. Using Critical Discourse Analysis on three key policy documents, the 2020–2035 Indonesian Education Roadmap, Ministerial Decree No. 56/2022, and the Merdeka Mengajar Platform Guide—the study uncovers underlying power dynamics and ideological assumptions embedded in the national digitalization agenda. The analysis identifies three dominant themes: (1) the hegemony of technological-efficiency narratives, reflected in notable lexical disparities (for example, “digital” appears far more frequently than “character” in the Roadmap); (2) disciplinary mechanisms enforced through legal obligations to access state-mandated digital platforms; and (3) an instrumental rationality that narrows education to the development of digital talent. The study concludes that digitalization in Merdeka Belajar is not merely a technological transition, but a contested arena where power relations shape and potentially marginalize humanistic educational values.